Analisis Faktor-Faktor yang Memengaruhi Minat Kunjungan Wisatawan Berdasarkan Komponen Destinasi Wisata di Kawasan Kuliner, Pasar Lama Tangerang - Antonius Rizki Krisnadi; Dessy Natalia (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Tourism in the city of Tangerang continues to experience an increase in the number of tourist visits. Based on data obtained from the Tangerang City Statistics Center, the number of tourist visits continues to increase, including an increase of 46.79% from 2017 to 2018. One of the most visited tourist destinations, culinary attractions in the Old Market, Tangerang. Culinary is a tourist attraction that is no longer a support in tourism, but instead becomes the main destination of tourists to carry out a tourism activity (Kristiana, Suryadi and Sunarya, 2018). Every tourist who will visit a tourist destination definitely needs a variety of services and facilities to reach that destination. This study aims to determine whether each dimension of attraction, accessibility, amenities, and ancillary services in the tourist destination component significantly influences the interest of tourists visiting the Tangerang Old Market Culinary Area. The theory used in this study is according to Cooper et al. in Anggela, Karini, & Wijaya (2017), which states that the components of a tourist destination have four dimensions, namely attraction, accessibilities, amenities, and ancillary services. Based on the results of the t test it is known that the dimension of attraction has a significant influence on the interest of tourist visits in the Tangerang Old Market Culinary Area, while the other three dimensions have no significant effect. Based on the results of the F Test simultaneously it is known that the component of the tourist destination has a significant influence on the interest of tourist visits in the Tangerang Old Market Culinary Area. Based on the Determination Coefficient Test results obtained by 38.6%. Suggestions from this research are so that the Culinary Area can be made more attractive and has special characteristics, adding detailed information about access to the location, completing facilities according to the needs of consumers and keeping it clean and completing additional services such as security posts and also Money Changer services.